Colposcopy in postmenopausal women: a challenging procedure - Kaur, Arshdeep; Singh, Gursewak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Introduction-carcinoma of cervix is the commonest cancer in Indian women. It constitutes 14%of the total population above age of 50 years. Atrophic changes in the genital tract causes problems in Pap smear as well as in the colposcopy. Methods: This is prospective observational study conducted in the department of obstetrics and gynecology of SGRDIMSR, Sri Amritsar, which comprised 30 cases of postmenopausal women referred for colposcopy. Inclusion criteria were complaints of post-menopausal bleeding, abnormal vaginal discharge, post coital bleeding, an abnormal PAP smear, an unhealthy-looking cervix. Women with history of any surgery on the cervix in the past three months or with obvious cervical cancer were excluded. Results: Patient with age group of 44-70 years were included, and maximum number of patients had complaint of post-menopausal bleeding (50%). 9 (30%) patients were positive for malignancy on histopathology, while with 9 (30%) false positive patients on colposcopy. Problems encountered while performing colposcopy includes cervix flushed with vagina, atrophy of introitus, bleeding from the cervix and relaxed vaginal walls. Use of various corrective measures were helpful to overcome the problems of colposcopy. Conclusions: It is an essential part of cervical screening programme, but it has some limitations and pitfalls which can lead to error in the diagnosis.